Typification of Quercus acuta Thunb. and Q. glauca Thunb. (Fagaceae) - Deng, Min; Li, Qiansheng; Coombes, Allen; Xu, Jin (Phytotaxa, 2013)
The lectotypes of Quercus acuta Thunb. and Q. glauca Thunb. are designated. The fine details of leaf epidermal features of the two species are elaborated for future comparison with other closely related species.